A Heterogeneous Dynamic Panel Approach to The Feldstein-Horioka Puzzle: Evidence from The European Union Countries - gündüz-özgür, şule (International Journal of Contemporary Economics and Administrative Sciences, 2023)
This study investigates whether the Feldstein and Horioka puzzle concerning domestic saving-investment relationship is supported by the data of the European Union (EU) countries using Cross-Sectional Augmented Error Correction Model (CS-ECM), Cross-Sectional ARDL (CS-ARDL) and Cross-Sectional Augmented Distributed Lag Model (CS-DL), the recent heterogeneous dynamic panel approaches which are robust to cross-sectional dependence and slope heterogeneity. The findings of the study imply high capital mobility for the EU countries over 1995-2021, and thus reject the existence of the Feldstein-Horioka puzzle.